2019
DOI: 10.1038/s41419-019-1919-0
|View full text |Cite
|
Sign up to set email alerts
|

ATF6 regulates the development of chronic pancreatitis by inducing p53-mediated apoptosis

Abstract: Chronic pancreatitis (CP) is a progressive, recurrent inflammatory disorder of the pancreas. Initiation and progression of CP can result from serine protease 1 (PRSS1) overaccumulation and the ensuing endoplasmic reticulum (ER) stress. However, how ER stress pathways regulate the development and progression of CP remains poorly understood. In the present study we aimed to elucidate the ER stress pathway involved in CP. We found high expression of the ER stress marker genes ATF6, XBP1, and CHOP in human clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Our data also indicated that TRAF2, one of the axis downstream molecules, was decreased with ambroxol administration, implying that IRE1α-TRAF2 axis was involved in ambroxol suppressing ER stress after ICH. Previous studies have demonstrated that the cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) can induce transcriptional activation of genes that ultimately lead to cell death [31,32]. Moreover, recent study has proven that CHOP silencing attenuates acute brain injury in rats after subarachnoid hemorrhage (SAH) [33], which is in line with our data that the expression of CHOP among lesions was downregulated when using ambroxol, compared to the ICH group.…”
Section: Discussionsupporting
confidence: 90%
“…Our data also indicated that TRAF2, one of the axis downstream molecules, was decreased with ambroxol administration, implying that IRE1α-TRAF2 axis was involved in ambroxol suppressing ER stress after ICH. Previous studies have demonstrated that the cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) can induce transcriptional activation of genes that ultimately lead to cell death [31,32]. Moreover, recent study has proven that CHOP silencing attenuates acute brain injury in rats after subarachnoid hemorrhage (SAH) [33], which is in line with our data that the expression of CHOP among lesions was downregulated when using ambroxol, compared to the ICH group.…”
Section: Discussionsupporting
confidence: 90%
“…Cyclin D1, an important regulator of the G1 phase of the cell cycle, increases in the pancreas of patients with CP, which may contribute to a hyperproliferative state in CP [35]. Inhibition of p53 expression decreased levels of in ammatory factors and suppressed progression of CP in the mouse model [36]. The chronic in ammatory process in CP markedly affects immune function in CP patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…ATF6-mediated signaling pathway of the UPR was involved in nonsteroidal anti-inflammatory drug-induced apoptosis 14 . Moreover, ATF6 promoted inflammation during chronic pancreatitis (CP) progression 15 . However, whether and how ATF6 participates in ER stress-mediated acinar apoptosis during SAP progression remains undiscovered.…”
Section: Introductionmentioning
confidence: 99%